Driving successful ageing in Singapore - MA, Kheng Min (Institutional Knowledge at Singapore Management University, 2021)
This case study is set in July 2021. It describes the ageing landscape in Singapore including the policies that have been developed to address Singapore’s rapidly ageing population and features the stories of two seniors. Since the 1980s, the Singapore Government had been developing plans and policies to help seniors, “to not just add years to life but add life to years” . The concept of successful ageing, defined by the five indicators – no major diseases, no disability, high cognitive function, physically fit and mobile, and active engagement with life, had been a focus area of the Singapore government for the past four decades. However, the rate of successful ageing had remained low, at only 25.4 percent. Given the rapidly ageing population, Lim Soon Meng, a director at Singapore’s Ministry of Health, wondered what else could be done to help more seniors age successfully? This case introduces the concept of the Third Age and invites discussion on the topic of successful ageing. Students will be able to 1) discuss the global ageing phenomenon related to ageism, economics of ageing, psychology of ageing and the notion of a Third Age, 2) analyse the challenges and lived experiences of third agers in Singapore, 3) discuss the concept of successful ageing, and apply the active ageing framework to address issues of social connectedness, 4) Evaluate active ageing policies and initiatives for older adults in Singapore.